Mikrotoponimia Kowalewic Nowych i Kowalewic Włościańskich w powiecie pułtuskim - Głogowska, Magda (Prace Językoznawcze, 2019)
Kowalewice Włościańskie and Kowalewice Nowe are two villages in Masovia region, district of Pułtusk, municipality of Świercze. They are inhabited mostly by farmers who inherit their farms. The total of 172 names of fields, meadows, forests, ponds, ditches and roads were collected in a field study. As a result of subsequent semantic analysis the following types of names have been distinguished: topographic (including locating, directional and descriptive names), possessive and culture-related. The majority (67%) of the analysed microtoponyms are topographic. Among these field, meadow and road names are the most numerous. Possesive names constitue an important part (30%) of all the collected names. The least represented are culture-related names, which constitute 3% of the collected microtoponyms. Among the microtoponyms from Kowalewice Włościańskie and Kowalewice Nowe there are primary (zero-affixation) and compound names, the latter being the largest group, which constitutes 81% of all the collected microtoponyms. The names constructed as adverbial phrases are the most productive type within this group. The primary names constitute 19% of the collected names of landscape features.